2022
DOI: 10.3390/molecules27030956
|View full text |Cite
|
Sign up to set email alerts
|

Umbrella Sampling Simulations of Carbon Nanoparticles Crossing Immiscible Solvents

Abstract: We use molecular dynamics to compute the free energy of carbon nanoparticles crossing a hydrophobic–hydrophilic interface. The simulations are performed on a biphasic system consisting of immiscible solvents (i.e., cyclohexane and water). We solvate a carbon nanoparticle into the cyclohexane layer and use a pull force to drive the nanoparticle into water, passing over the interface. Next, we accumulate a series of umbrella sampling simulations along the path of the nanoparticle and compute the solvation free e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 57 publications
0
1
0
Order By: Relevance
“…In this context, molecular dynamics simulations have convinsingly verified that the favored reaction coordinate for the delamination of layered materials is on the shear direction [32] . In particular, steered molecular dynamics (MD) have shown that it requires essentially less force to pull the exfoliating graphene sheet parallel (shear) to the basal plane of the graphite than perpendicular to it [12,33,34] . Molecular simulations are capable to readily identify the favorable reaction coordinate and required force in transition processes like LPE.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, molecular dynamics simulations have convinsingly verified that the favored reaction coordinate for the delamination of layered materials is on the shear direction [32] . In particular, steered molecular dynamics (MD) have shown that it requires essentially less force to pull the exfoliating graphene sheet parallel (shear) to the basal plane of the graphite than perpendicular to it [12,33,34] . Molecular simulations are capable to readily identify the favorable reaction coordinate and required force in transition processes like LPE.…”
Section: Introductionmentioning
confidence: 99%
“…[32] In particular, steered molecular dynamics (MD) have shown that it requires essentially less force to pull the exfoliating graphene sheet parallel (shear) to the basal plane of the graphite than perpendicular to it. [12,33,34] Molecular simulations are capable to readily identify the favorable reaction coordinate and required force in transition processes like LPE. Nevertheless, their primary advantage lies in offering microscopic insights and delving into the thermodynamic aspects that govern such processes, including evaluations of the free energy.…”
Section: Introductionmentioning
confidence: 99%
“…The subsequent stage involves dividing the range of ξ into discrete intervals, dξ, and introducing a biasing potential (harmonic potential) within each interval to improve the sampling further. This method is called umbrella sampling. Umbrella sampling allows for getting as many sample points as needed at each location ξ along the interval of interest. We get relatively uniform sampling within each interval, and by doing so, we obtain excellent statistics even in transition regions that are rarely visited otherwise.…”
Section: Introductionmentioning
confidence: 99%